Dukungan Sosial Terhadap Kualitas Hidup Kelompok Tuli Di Majelis Ta’lim Tuli Indonesia - Fairuz Tsina; Ati Kusmawati (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
The Deaf community, as a minority group, often faces negative stigma from people in their surroundings due to differences in communication culture between Deaf and hearing people. Discriminatory treatment like this can lead to problems such as low quality of life. This is evident in the Deaf community within the Indonesian Deaf Majelis Ta'lim, which was founded out of the concern of its founder who saw the lack of understanding among Deaf Muslims in understanding their religion and God. This study aims to determine the influence of social support on the quality of life of the Deaf community in the Indonesian Deaf Majelis Ta'lim. The study used a quantitative method with 30 Deaf subjects aged over 17 years who have experienced hearing loss since birth or due to other factors. Data collection techniques were carried out using classical assumption tests by testing for normality and linearity, and hypothesis testing using simple linear regression analysis using SPSS 26 for windows. The results showed that the correlation coefficient (R) was 0.769, and the coefficient of determination (R Square) was 0.591, indicating that about 59.1% of the variation in quality of life can be explained by social support. The t-test showed that the calculated t-value of 6.357 exceeded the table t-value of 2.048, which implies that the social support variable (X) has a significant influence on the quality of life (Y).